Trapped without a diagnosis: Tumour necrosis factor receptor-associated periodic syndrome (TRAPS). - Kirresh,A; Everitt,A; Kon,OM; DasGupta,R; Pickering,MC; Lachmann,HJ (Practical Neurology, 2016)
Tumour necrosis factor receptor-associated periodic syndrome (TRAPS) is an autosomal dominant condition caused by mutations in the TNFRSF1A gene. It is characterised by recurrent episodes of myalgia, followed by prolonged fever, migratory rashes, headache, serositis, arthralgia, abdominal pain and periorbital oedema. We describe a 49-year-old man with a self-limiting episode of paraparesis who reported recurrent bouts of abdominal symptoms and headaches since childhood. He had a persistent inflammatory response with night sweats and weight loss. We diagnosed TRAPS 2years after having identified a TNFRSF1A gene mutation. His symptoms and inflammatory response resolved dramatically with the interleukin-1 receptor antagonist anakinra.